Analisis Faktor Kepatuhan Berobat Penderita Tuberculosis Paru di Bandung - Upik Rahmi (Fakultas Ilmu Kesehatan, 2020)
ABSTRACT Tuberculosis (TB) is one of the public health problems that cannot be overcome. The problem is caused by several factors, one of which is the non-compliance of patients with treatment. In Indonesia, the incidence of TB cases is 842,000 per year and notification of TB cases is 569,899 cases, so there are still around 32% of the cases that have not been verified either unreached, undetected or not reported. From this incident rate the TB burden is calculated in each province and district / city, (Indonesia, 2019). Purpose: Identify factors related to adherence to the treatment of pulmonary TB patients in the working area of ​​Garuda Bandung Puskesmas. Method: This is an analytic case study with a case control design. The sample of this study was 43 pulmonary TB patients taken in total who failed and were removed from treatment in 2017. The research instrument used a questionnaire. Data analysis using chi square. Results: The most dominant factors affecting adherence to treatment among pulmonary TB patients were Gender P value (0.014) and occupational Pvalue (0.025) where p <0.05 while factors not related to medication adherence were age, knowledge, education, and family income, p> 0.05. Conclusion: Gender and occupation have a significant relationship to tuberculosis treatment adherence, while age, knowledge and family income have no significant relationship to tuberculosis patient adherence. Keywords: Pulmonary tuberculosis, compliance, Medicine